Human Studies and the Horizons of Digital Transformation - 10th International Scientific, Conference (lark, 2026)
The conference aimed to establish a systematic academic framework for studying digital transformation in the humanities, outlining its epistemological foundations and applied approaches in fields such as applied philosophy, translation, social sciences, literature, languages, media, and public relations, thereby contributing to the development of scientific research and enhancing cognitive integration in line with the requirements of digital transformation in human studies. It also discussed mechanisms for employing modern technologies to advance scientific research, strengthen the integration of human knowledge and technology to meet contemporary demands, support scientific research, and expand the horizons of academic cooperation.